Severe neonatal hypoglycaemia and intrapartum glycaemic control in pregnancies complicated by type 1, type 2 and gestational diabetes. Issue 1 (11th October 2019) - Yamamoto, J. M.; Donovan, L. E.; Mohammad, K.; Wood, S. L.
What's new?: In pregnancies with diabetes, guidelines recommend tight intrapartum glycaemic control based on the theory that this will decrease the risk of neonatal hypoglycaemia; however, the evidence supporting this theory is conflicting. In this large cohort of women with type 1, type 2 and gestational diabetes, there was no significant association between in‐target intrapartum glycaemic control and severe neonatal hypoglycaemia after adjustment for neonatal confounders. Future trials should consider whether more relaxed intrapartum glycaemic targets may be safer in women with diabetes in pregnancy and yield similar neonatal results or outcomes. Abstract: Aims: To determine if in‐target intrapartum glucose control is associated with neonatal hypoglycaemia in women with type 1, type 2 or gestational diabetes. Methods: This was a retrospective cohort study of pregnant women with diabetes and their neonates. The primary exposure was in‐target glucose control, defined as all capillary glucose values within the range 3.5–6.5 mmol/l during the intrapartum period. The primary outcome, neonatal hypoglycaemia, was defined as treatment with intravenous dextrose therapy. Multiple logistic regression was used to examine the association between maternal intrapartum glycaemic control and neonatal hypoglycaemia, adjusting for covariates. Results: Intrapartum glucose testing was available for 157 (86.3%), 267 (76.3%) and 3256 (52.4%) women with type 1, type 2 and gestational diabetes, respectively. In the univariate analysis, in‐target glycaemic control was significantly associated with neonatal hypoglycaemia in women with gestational diabetes, but not in women with type 1 or 2 diabetes. However, after adjustment for important neonatal factors (large for gestational age, preterm delivery and infant sex), intrapartum in‐target glycaemic control was not significantly associated with neonatal hypoglycaemia in women regardless of diabetes type [adjusted odds ratios 0.4 (95% CI 0.1, 1.4), 0.7 (95% CI 0.3, 1.3) and 0.7 (95% CI 0.5, 1.0) for women with type 1, type 2 and gestational diabetes, respectively]. Conclusions: There was no significant association between in‐target glycaemic control and neonatal hypoglycaemia after adjustment for neonatal factors. Given the high risk of maternal hypoglycaemia and the resources required, future trials should consider whether more relaxed intrapartum glycaemic targets may be safer and yield similar neonatal outcomes.